2020
DOI: 10.1088/2053-1583/ab8268
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced phase transition in CrI3 bilayers

Abstract: A monolayer of CrI3 is a two-dimensional crystal in its equilibrium configuration is a ferromagnetic semiconductor. In contrast, two coupled layers can be ferromagnetic, or antiferromagnetic depending on the stacking. We study the magnetic phase diagram upon the strain of the antiferromagnetically coupled bilayer with C2/m symmetry. We found that strain can be an efficient tool to tune the magnetic phase of the structure. A tensile strain stabilizes the antiferromagnetic phase, while a compressive strain turns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 60 publications
(109 reference statements)
10
34
0
Order By: Relevance
“…2(e). This magnetic configuration is the same as that reported recently [28]. The trend of the strain-dependent exchange interactions can be understood qualitatively as follows.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2(e). This magnetic configuration is the same as that reported recently [28]. The trend of the strain-dependent exchange interactions can be understood qualitatively as follows.…”
Section: Resultssupporting
confidence: 85%
“…Therefore, strong PMA and FM ordering are desired and it is important to explore strategies to control the MA and to enhance T C [23]. Although theoretical study of the effect of strain on the MA of the monolayer CrI 3 has been done recently [24][25][26][27], systematic theoretical investigation of the electronic and magnetic properties including the MA and magnetic ordering of the bilayer CrI 3 under strain is still lacking [28].…”
Section: Introductionmentioning
confidence: 99%
“…The AB-like stakings have the lowest energy (table I); these configurations favor compact structures. This behavior has also been observed in other 2D systems 9,14,43 . The variations in the lattice vectors in table I are small enough to be negligible, thus have no impact on the stability order of the system.…”
Section: Equilibrium Configurationsupporting
confidence: 82%
“…Morell et al investigated the magnetic‐phase transition of antiferromagnetically coupled bilayer CrI 3 under strain. It was found that tensile strain could stabilize the antiferromagnetic phase, while compressive strain made the system transform into ferromagnetic phase, which was related to the strain‐induced horizontal shift of interlayer 121 …”
Section: Modulation Of Properties Based On Strain Engineeringmentioning
confidence: 99%